Effectiveness of Internal Audit and Oversight at Central Banks : Safeguards Findings - Chamoun, Elie (IMF Working Papers; Working Paper ;, 2018)
Experience under the safeguards policy has shown that central banks continued to strengthen their safeguards frameworks, but that vulnerabilities prevailed in the areas of internal audit and oversight by the audit committee (AC). This paper takes steps to help unravel why this was the case, based on analysis of safeguards findings in these areas during the period April 2010 to December 2017 (covering 111 assessments at 64 central banks). Based on this analysis, it presents the key attributes that determine the effectiveness of internal audit and the AC. It also argues that, an effective internal audit function, coupled with strong oversight by a high-performing AC are key enablers of good governance.